Nanogap-based all-electronic DNA sequencing devices using MoS2monolayers - Perez, A. [UNESP]; Amorim, Rodrigo G.; Villegas, Cesar E. P.; Rocha, Alexandre R. [UNESP] (Royal Society of Chemistry (RSC), 2020)
The realization of nanopores in atom-thick materials may pave the way towards electrical detection of single biomolecules in a stable and scalable manner. In this work, we theoretically study the potential of different phases of MoS2 nanogaps to act as all-electronic DNA sequencing devices. We carry out simulations based on density functional theory and the non-equilibrium Green's function formalism to investigate the electronic transport across the device. Our results suggest that the 1T′-MoS2 nanogap structure is energetically more favorable than its 2H counterpart. At zero bias, the changes in the conductance of the 1T′-MoS2 device can be well distinguished, making possible the selectivity of the DNA nucleobases. Although the conductance fluctuates around the resonances, the overall results suggest that it is possible to distinguish the four DNA bases for energies close to the Fermi level.